Efficacy of Sin Tax and Recommendations for Implementation of Tobacco Tax Regimen in Pakistan - Munir, Saqib; Waheed, Khawaja Zeeshan; Shakeel, Muhammad (iRASD Journal of Economics, 2022)
Behavioural economics is a comparatively recent topic that challenges the mainstream economics’ basic assumptions. It emphasizes that humans aren't always rational, aren't always self-interested, and don't always have time-consistent preferences. A sin tax is a type of sumptuary tax that is imposed on some typically socially prohibited items and services, like liquor, cigarettes, SSBs, and gambling. Sumptuary taxes, which are a type of sumptuary regulation, are presumably meant to reduce transactions involving something that society finds undesirable. Tobacco usage continues to be one of Pakistan's most pressing development concerns. Tobacco products usage is the foremost reason of death from non-communicable diseases (NCDs), such as cancer, lingering breathing illnesses, and cardio vascular diseases (CVDs). Tobacco taxation, which is widely recognized as a fundamental component of tobacco regulating policy, is utilized in Pakistan to combat tobacco use with the dual goals of public health promotion and income collection. Behind the scenes, the tobacco industry's success is based on a lack of understanding of real economics. Despite the fact that tobacco usage is linked to a number of negative health outcomes, higher health costs, and overworked health systems, the tax incomes it creates often encourage policy inertia in low-income countries like Pakistan. It is important that while taxing the sin of tobacco consumption the basic goal should be discouraging the behaviour and not income generation.